Embedding the MatPLC - Mário de Sousa (2005)
The MatPLC is an international project to develop a program similar to a PLC (Programmable Logic Controller) for POSIX operating systems. It is an open source application consisting of a core, generic modules, and tools for creating custom modules. Since many control and monitoring systems are distributed in nature, they require that the application be running on an embedded system capable of withstanding harsh environments. This paper describes the porting ofthe MatPLC code base to a commercial embedded system running on a PowerPC CPU. Time measurements were taken to determine whether the resulting code would be suitable for control applications.